ANALISIS WARNA DAN BENTUK PADA INTERIOR PRODIA CHILDREN’S HEALTH CARE TERHADAP PSIKOLOGI ANAK - Niken Laksitarini; Agus Dody Purnomo (Universitas Trisakti, 2022)
The use of color in the interior has a very important role. Color is a basic element of an interior space design. The use of the right color will be able to motivate or even reduce a human psychological condition. Especially if the health clinic has been identified by a small child with something scary, because it is often associated with needles, blood and disease. Prodia Children’s Health Care as a service provider in the field of health specializing in the services of young children, seeks to change that paradigm. Qualitatively, this study aims to identify the effect of the color used in the interior of Prodia Children, s Health Care on children's psychology. The findings obtained are expected to be input and consideration in the planning, design and development of special health facilities for children in the future.Keywords: color, interior, children